ADAPTIVE ANALYSIS OF HIGHLY HETEROGENEOUS SINUSOIDAL TRAJECTORIES - P. Grisanti; M. A. Bettera Marcat; E. Pulgar; V. I. Marconi (Anales (Asociación Física Argentina), 2023)
The study of sperm motility offers multiple applications in reproductive medicine, as well as in the aquaculture and livestock industrie. Aiming to achieve a population motility characterization with high precision and automatization, a software was developed in order to obtain good motility parameters from their trajectories: mean velocity, heading frequency and amplitude. The development requires only one adjustable parameter, an initial time window for averaging, which is optimized recursively for each cell. When it is applied to aquatic spermatozoa recorded at 400 fps, it proves to be robust and adaptable to populations with high heterogeneity in their motility parameters.